2015
DOI: 10.5539/ibr.v8n3p208
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Training and Job Satisfaction on Turnover Intentions?

Abstract: The literature of fast food franchises in Saudi Arabia has reported a lack of research on the topic of employee training. This study pursues to add literature and findings in fast food franchises sector by examining the impact of effective training and coworker support for training on turnover intentions among the employees of fast food franchises in Saudi Arabia. A total number of 350 questionnaires were distributed among the employees working in different fast food franchises of Saudi Arabia, out of which 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 63 publications
8
27
1
4
Order By: Relevance
“…Finally, it is essential to reduce the high rates of turnover in the program among psychologists and social workers in order to guarantee the appropriation of knowledge and take advantage of the accumulated experience derived from the service provision [ 45 ]. The managers of the program should promote the continuous training of professionals, the improvement of working conditions, and the actions aimed at increasing empowerment in the workplace to reduce turnover rates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is essential to reduce the high rates of turnover in the program among psychologists and social workers in order to guarantee the appropriation of knowledge and take advantage of the accumulated experience derived from the service provision [ 45 ]. The managers of the program should promote the continuous training of professionals, the improvement of working conditions, and the actions aimed at increasing empowerment in the workplace to reduce turnover rates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…EDP is not the only reason for organizational commitment but it can also assist in enhancing employees’ efficiency (Tansky & Cohen, ). A proper EDP with supported tools will help the organization to retain their skilled employees (Jehanzeb et al ., ). Hence, it may be assumed that EDPs will positively influence job satisfaction and organizational commitment (Jehanzeb et al ., ; Mullen et al ., ; Wagner, ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Scholars in human resources management have linked employee development with skill enhancement, improved productivity, decreased turnover intentions and increased employee participation (Jehanzeb & Bashir, ; Rahman & Nas, ). Most studies have concluded that job satisfaction has a positive impact on workplace outcomes (Jehanzeb et al ., ; Samad & Ysuuf, ), such as increased employee commitment, workplace harmony, increased productivity, creativity and innovation, employee support and organizational citizenship behaviour (OCB) (Chiaburu et al ., ; Jehanzeb et al ., ; Ok & Vandenberghe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, improved openings in organisations often favour the supervisors, as their labourers are convinced to be more helpful, which results in benefits. In this cooperation, the likelihood that a specialist will remain with an organisation is augmented as well (Jehanzeb et al, 2015). Considering the capacities acquired and dominated, she or he will undoubtedly make headway that directly affects various levels of earnestness.…”
Section: Literature Reviewmentioning
confidence: 99%